Dynamic adaptation and deployment of distributed components in Hadas. - Ben-Shaul, I. (IEEE Transactions on software engineering)
Global network connectivity has enabled accessibility to a wide range of geographically dispersed services. By encapsulating and representing such services as components, they can be effectively composed into sophisticated wide-area applications that otherwise would be much harder to build. This paper presents a component model for encapsulating such services and a composition model for assembling encapsulated and possibly active services into new applications, while preserving the administrative autonomy of sites and individual components. The component model is dynamically and self-adaptable, allowing for the adjustment of structure and behavior of autonomous components to changing or previously unknown contexts in which they need to operate. The composition model includes a set of protocols that enable us to dynamically deploy live components into remote sites and to dynamically reconfigure the deployment scheme through reflective stubs termed Ambassadors. The component and composition models have been fully implemented in Hadas, which also includes a host of tools for the creation, deployment, and composition of autonomous components